Strategi Pengembangan Usaha Ayam Ras Petelur di UD Selanjar Poultryshop Desa Pakel Kecamatan Ngantru Kabupaten Tulungagung - Ibnu Rifa, Ahmad Faiz Salsabila; Winarno, Sri Tjondro; Roidah, Ida Syamsu (Universitas Batanghari Jambi, 2025)
This research aims to identify internal factors (strengths, weaknesses) and external factors (opportunities, threats), analyze alternative strategies, and determine strategic priorities that will be applied to the laying chicken farming business at UD. Selanjar Poultryshop Pakel Village, Ngantru District, Tulungagung Regency. The method chosen for sampling used a purposive sampling method with 5 respondents and descriptive analysis was used to help interpret the results of profit calculations and business development strategies. The research results show that in the internal environment, the main strength factor that has the most influence is Good Product Quality, while the main weakness factor that must be addressed immediately is Fluctuating Production Costs. External Environment, the main opportunity factor that must be utilized properly is the High Demand for Eggs, while the main threat factor that must be overcome is Market Prices which tend to be unstable. The results of the I-E matrix analysis state that the company's position is in cell V, namely the strategy used in this cell is market penetration and product development. The results of the SWOT analysis show that there are seven alternative strategies that can be applied to the organization. The results of the QSPM matrix analysis produce two priority strategies, namely optimizing production management in dealing with price fluctuations and market demand and expanding and improving business partner ties. These two strategies are recommendations from researchers to be applied to companies.